Spatial, temporal, and vertical variability of polar stratospheric ozone loss in the Arctic winters 2004/05-2009/10 - Kuttippurath, Jayanarayanan; Godin-Beekmann, Sophie; Lefèvre, Franck; Goutail, Florence (Atmospheric Chemistry and Physics, 2010)
International audience The stratospheric ozone loss during the Arctic winters 2004/05-2009/10 is investigated by using high resolution simulations from the chemical transport model Mimosa-Chim and observations from Microwave Limb Sounder (MLS) on Aura by the passive tracer technique. The winter 2004/05 was the coldest of the series with strongest chlorine activation. The ozone loss diagnosed from both model and measurements inside the polar vortex at 475 K ranges from ~1-0.7 ppmv in the warm winter 2005/06 to 1.7 ppmv in the cold winter 2004/05. Halogenated (chlorine and bromine) catalytic cycles contribute to 75-90% of the accumulated ozone loss at this level. At 675 K the lowest loss of ~0.4 ppmv is computed in 2008/09 from both simulations and observations and, the highest loss is estimated in 2006/07 by the model (1.3 ppmv) and in 2004/05 by MLS (1.5 ppmv). Most of the ozone loss (60-75%) at this level results from cycles catalysed by nitrogen oxides (NO and NO2) rather than halogens. At both 475 and 675 K levels the simulated ozone evolution inside the polar vortex is in reasonably good agreement with the observations. The ozone total column loss deduced from the model calculations at the MLS sampling locations inside the vortex ranges between 40 DU in 2005/06 and 94 DU in 2004/05, while that derived from observations ranges between 37 DU and 111 DU in the same winters. These estimates from both Mimosa-Chim and MLS are in general good agreement with those from the ground-based UV-VIS (ultra violet-visible) ozone loss analyses for the respective winters.